2012
DOI: 10.4161/mabs.4.1.18748
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of host-cell proteins in biotherapeutic proteins by comprehensive online two-dimensional liquid chromatography/mass spectrometry

Abstract: (2012) Analysis of host-cell proteins in biotherapeutic proteins by comprehensive online two-dimensional liquid chromatography/mass spectrometry, mAbs, 4:1, 24-44,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
150
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(162 citation statements)
references
References 41 publications
7
150
0
Order By: Relevance
“…Even after sophisticated purification steps, low levels of HCPs may still remain in a final purified biotherapeutic,29 although it is important to note that the ratio of DnaK : scFv used in these experiments (1 : 1000) was higher than would be expected in most biotherapeutic preparations used clinically. Accepted limits of HCPs are generally 1–100 parts per million 29. However, 1 part per million HCPs could result in 0·1 μg HCP in a 100‐mg dose (biotherapeutics given to patients can reach doses well above 100 mg30, 31).…”
Section: Discussionmentioning
confidence: 96%
“…Even after sophisticated purification steps, low levels of HCPs may still remain in a final purified biotherapeutic,29 although it is important to note that the ratio of DnaK : scFv used in these experiments (1 : 1000) was higher than would be expected in most biotherapeutic preparations used clinically. Accepted limits of HCPs are generally 1–100 parts per million 29. However, 1 part per million HCPs could result in 0·1 μg HCP in a 100‐mg dose (biotherapeutics given to patients can reach doses well above 100 mg30, 31).…”
Section: Discussionmentioning
confidence: 96%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In this methodology, proteins are first digested enzymatically. The resulting peptides are then separated (usually by liquid chromatography), and subsequently detected by mass/ charge via a mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6]11,14 Since HCPs are several orders of magnitude lower in concentration compared to the protein therapeutic, 2-dimensional LC separation helps increase the sensitivity of HCP detection. HCP quantitation is then achieved typically by spiking in one or more protein standards at known concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of an effort to help users understand the conditions under which 2D-LC provides more resolving power than 1D-LC separations for peptide analyses, the Heinisch group recently demonstrated that the peak capacity of 2D-LC separations is superior to that of 1D-LC separations for analysis times longer than about five minutes [18]. In the area of Host Cell Protein (HCP) analysis, Donenau and coworkers have demonstrated the use of heartcutting 2D-LC [19,20] and offline comprehensive 2D-LC [21] to detect trace-level peptide markers of HCPs. This is very important to quality assurance for biotherapeutic mAbs.…”
Section: Peptide Level Analysismentioning
confidence: 99%